2007
DOI: 10.1111/j.1365-2141.2007.06829.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of new bone formation by the proteasome inhibitor, bortezomib: implications for myeloma bone disease

Abstract: SummaryImpaired bone formation contributes to the lack of bone healing in multiple myeloma and there is a need for agents with bone anabolic properties to reverse the bone deficit in patients. Bortezomib, a proteasome inhibitor with antitumour efficacy in myeloma patients, enhanced new bone formation in mouse calvarial cultures; this effect was blocked by dickkopf 1(Dkk1), an antagonist of Wnt signalling implicated in myeloma bone disease. Bortezomib inhibited Dkk1 expression in calvariae and bone marrowderive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 14 publications
6
79
0
1
Order By: Relevance
“…BTZ treatment also enriched the bone remodeling pathway involving IFNB1, TNFSF11 and FOS (Table 1). This is in agreement with a previous report [43] that BTZ might promote synovial osteoclastogenesis and bone destruction through upregulating the expression of c-FOS and RANKL/TNFSF11. Our data showed that SOST, a downstream target in the BMP (bone morphogenetic protein) signaling pathway, was also stabilized by BTZ ( Figure 4B and 4C).…”
Section: Gene Ontology and Pathway Analysessupporting
confidence: 94%
“…BTZ treatment also enriched the bone remodeling pathway involving IFNB1, TNFSF11 and FOS (Table 1). This is in agreement with a previous report [43] that BTZ might promote synovial osteoclastogenesis and bone destruction through upregulating the expression of c-FOS and RANKL/TNFSF11. Our data showed that SOST, a downstream target in the BMP (bone morphogenetic protein) signaling pathway, was also stabilized by BTZ ( Figure 4B and 4C).…”
Section: Gene Ontology and Pathway Analysessupporting
confidence: 94%
“…37 In addition to its well-documented antimyeloma effects, bortezomib has also been shown to stimulate osteoblasts. [38][39][40][41][42][43][44] In its current front-line trial comparing lenalidomide-dexamethasone with lenalidomidedexamethasone plus bortezomib, the Southwest Oncology Group evaluates, via serial MRI and PET-CT scanning, whether the anticipated clinical benefit of bortezomib can be linked to faster onset and higher frequency of imaging-defined CR. For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…41 In addition to its direct antitumor effects, Bzb has also been shown to induce OB differentiation in mouse and human MSCs in vitro 2,3 and in animal models in vivo. 3,4 Moreover, Bzb treatment has been associated with the elevation of bone markers in MM patients, which has also been linked to improved outcome. 1,[42][43][44][45][46] It is not certain how the increase in bone markers induced by Bzb is related to improved outcome but may be related to the anti-MM effects of OBs and the suppression of osteoclasts that support MM growth 47 and/or the suppression of interleukin-6 production by increased differentiation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Bzb has been reported to regulate osteogenesis via the induction of BMP-2 expression, 3 increasing Runx2 transcriptional activity 2 and stabilization of Runx2 protein. 5,6 It is important to note, however, that Bzb can also induce OB differentiation in Runx2 null mice.…”
Section: Introductionmentioning
confidence: 99%